Sex-Specific Brain Responses to Imaginary Dance but Not Physical Dance: An Electroencephalography Study of Functional Connectivity and Electrical Brain Activity - Wind, Johanna; Horst, Fabian; Rizzi, Nikolas; John, Alexander; Kurti, Tamara; Schöllhorn, Wolfgang I. (Frontiers in Behavioral Neuroscience, 2021)
To date, most neurophysiological dance research has been conducted exclusively with female participants in observational studies (i.e., participants observe or imagine a dance choreography). In this regard, the sex-specific acute neurophysiological effect of physically executed dance can be considered as a widely unexplored field of research. The current study examines the acute impact of a modern jazz dance choreography on brain activity and functional connectivity using electroencephalography (EEG). In a within-subject design, eleven female and eleven male participants were examined under four test conditions: physically dancing the choreography with and without music and imagining the choreography with and without music. Prior to the EEG measurements, participants acquired the choreography over three weeks with one session per week. Subsequently, participants conducted all four test conditions in a randomised order on a single day, with EEG measurements taken before and after each condition. Differences between male and female participants were established in a brain activity and a functional connectivity analysis in the condition imagined dance without music. No differences between sexes were found in the other three conditions (physically executed dance with and without music as well as imagined dance with music). Physically dancing and music seem to have sex-independent effects on the human brain. However, thinking of dance rather seems to be sex specific. The results point to a promising approach to decipher gender-specific differences in the use of dance or music in a differentiated way. The approach could further be used to achieve a more group-specific or an even more individualized and situationally adapted use of dance interventions, e.g. in the context of sports, physical education or therapy. To what extent the identified differences are due to culturally specific attitudes in the gender-specific contact with dance and music needs to be clarified in future research. With this study a beginning has been made.